2007
DOI: 10.1007/s00228-007-0283-7
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug effects in elderly people – a disparity between clinical examination and adverse effects self-reported by the patient

Abstract: There was a great disparity between the adverse effects identified by the physician and those reported by the patients themselves. Based on our results, it would appear that elderly people tend to neglect adverse drug effects and may consider them to be an unavoidable part of normal ageing. Therefore, physicians should enquire about possible adverse effects even though elderly patients may not complain of any drug-related problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…Physicians mainly report serious ADEs, 22 suggesting that they are more focused on those ADEs that they judge as clinically relevant, necessitating treatment modification. 23,24 Modification of medication prescribed by physicians in case of mild ADEs, even after multiple reporting, is shown to be relatively low (only in 38% of the cases). 4 Our results suggest that the meaning of a Bsignificant health problem[ as a justification of discontinuation or uptitration as mentioned in the European guidelines of HF treatment 1 may be put into a broader perspective including the more mild ADEs, with patients' tolerance as cutoff.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians mainly report serious ADEs, 22 suggesting that they are more focused on those ADEs that they judge as clinically relevant, necessitating treatment modification. 23,24 Modification of medication prescribed by physicians in case of mild ADEs, even after multiple reporting, is shown to be relatively low (only in 38% of the cases). 4 Our results suggest that the meaning of a Bsignificant health problem[ as a justification of discontinuation or uptitration as mentioned in the European guidelines of HF treatment 1 may be put into a broader perspective including the more mild ADEs, with patients' tolerance as cutoff.…”
Section: Discussionmentioning
confidence: 99%
“…During the past few decades, the use of medicines by the elderly has changed markedly, with both the total use of medicines and the prevalence of polypharmacy increasing in this age group [24,25]. The average number of drugs regularly taken per elderly persons has been reported to range from 3.6 to 6.7 and tends to increase after admission to institutionalized care [26]. …”
Section: Introductionmentioning
confidence: 99%
“…It is well established that polypharmacy increases the risk of undesired drug interactions [27] and adverse effects[28], which are major contributors to a decline in the quality of life [26]. Moreover, physiologic changes associated with aging affect the pharmacokinetics and pharmacodynamics of drugs, placing this population at increased risk for drug-related problems [29].…”
Section: Introductionmentioning
confidence: 99%
“…19 Patient-related factors are also important, where elderly patients may consider observed symptoms or problems as an unavoidable part of aging. 20 Second, when problems are reported by patients, health care providers may fail to acknowledge the adverse effects or focus mainly on adverse effects which are clinically relevant and necessitate immediate intervention. 20,21 A study on doctors' attitudes revealed that up to 20% of the respondents did not consider medication adverse effects a concern related to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…20 Second, when problems are reported by patients, health care providers may fail to acknowledge the adverse effects or focus mainly on adverse effects which are clinically relevant and necessitate immediate intervention. 20,21 A study on doctors' attitudes revealed that up to 20% of the respondents did not consider medication adverse effects a concern related to clinical practice. 22 During encounters on medication, patients were usually the ones who raised concerns about medication problems such as adverse effects.…”
Section: Discussionmentioning
confidence: 99%